Representations of the function during teaching: A look from teacher’s specialized knowledge and mathematical work - Espinoza Vásquez, Gonzalo; Verdugo-Hernández, Paula (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
This study aims at teachers’ knowledge and mathematical work during function representations teaching through the joint use of two theoretical models. In concrete, a session for the 1st year of secondary education (14-15 years old) given by a mathematics teacher with the category of expert is analyzed. The results show the relationship between the mathematical work proposed in the classroom and the knowledge that this organization allows, contributing elements to the understanding of the teaching practice.